226k views
2 votes
Which expressions in the picture are equivalent to (v^-1)^1/9? Choose all answers that apply:

Which expressions in the picture are equivalent to (v^-1)^1/9? Choose all answers-example-1
User DEH
by
5.7k points

2 Answers

0 votes

Answer:

All of them: A, B, and C

Explanation:

User Dave Lillethun
by
5.8k points
0 votes

Answer:

A, B, and C

Explanation:

Recall the exponent property
(a^b)^c=a^{(b\cdot c).

Therefore,


(v^(-1))^(1/9)=(v^(1/9))^-1=v^(-1/9)

In addition, fraction exponents can be written as radicals such that:


a^(b/c)=\sqrt[c]{a^b}

Thus,
(\sqrt[9]{v})^(-1)=(v^(1/9))^(-1)=(v^(-1))^(1/9).

Therefore, answer choices A, B, and C are correct.

User Shadrx
by
6.2k points